Midterm outcomes of posterior cruciate ligament substituting total knee arthroplasty - Unat, Beytullah; Karakurum, Gunhan (Annals of Medical Research, 2023)
Aim: In the present study, it is aimed to retrospectively investigate and present the midterm results of the cases with posterior cruciate ligament (PCL) substituting total knee arthroplasty. Materials and Methods: In this study, we included a total of 61 patients with 80 knees who underwent PCL-substituting total knee arthroplasty between July 2006 and June 2012. Results: 52 patients were female and 9 were male. The mean age of patients was 65.4 (42-85) years and the mean follow up period was 32.6 (12-72) months. Patients were evaluated according to the American Knee Society Score for knee score and knee functional score. Radiological evaluation was performed according to Total Knee Arthroplasty Radiological Evaluation criteria. Knee score was 38-71 (mean 43.7) prior to the surgery and 78-100 (mean 95) subsequently. 69 knee (86,25%) had perfect knee scores and 11 knee (13.75%) had good scores. Functional score was 10-60 (mean 35.08) prior to the surgery and 60-100 (mean 82.2) subsequently. In the evaluation according to the functional knee score, we obtained perfect results in 45 knee (56.25%) and good results in 29 knees (36.25%) and moderate results in 6 knees (7.5%). Patients had a mean 9.7o varus (8o valgus – 20o varus) prior to the surgery and mean 4.75o valgus (2o varus – 10o valgus) alignment was obtained subsequently to surgery. In 1 case revision arthroplasty was performed due to late deep infection. In 1 case insert replacement was performed due to insert fracture due to trauma. As a result of our PCL substituting total knee arthroplasty applications, we obtained 86.25%perfect knee score and 56.25%perfect functional score. Conclusion: PCL substituting total knee arthroplasty is a favorable orthopedic surgical intervention when preformed with adequate preoperative preparations and cautious surgical techniques with appropriate patient choice.